Antimicrobial peptides as a promising treatment option against Acinetobacter baumannii infections. (September 2020) - Neshani, Alireza; Sedighian, Hamid; Mirhosseini, Seyed Ali; Ghazvini, Kiarash; Zare, Hosna; Jahangiri, Abolfazl
Abstract: Background: With the increasing rate of antibiotic resistance in Acinetobacter, the World Health Organization introduced the carbapenem-resistant isolates in the priority pathogens list for which innovative new treatments are urgently needed. Antimicrobial peptides (AMPs) are one of the antimicrobial agents with high potential to produce new anti- Acinetobacter drugs. This review aims to summarize recent advances and compare AMPs with anti- Acinetobacter baumannii activity. Methods: Active AMPs against Acinetobacter were considered, and essential features, including structure, mechanism of action, anti- A. baumannii potent, and other prominent characteristics, were investigated and compared to each other. In this regard, the Google Scholar search engine and databases of PubMed, Scopus, and Web of Science were used. Results: Forty-six anti- Acinetobacter peptides were identified and classified into ten groups: Cathelicidins, Defensins, Frog AMPs, Melittin, Cecropins, Mastoparan, Histatins, Dermcidins, Tachyplesins, and computationally designed AMPs. According to the Minimum Inhibitory Concentration (MIC) reports, six peptides of Melittin, Histatin-8, Omega76, AM-CATH36, Hymenochirin, and Mastoparan have the highest anti- A. baumannii power against sensitive and antibiotic-resistant isolates. All anti- Acinetobacter peptides except Dermcidin have a net positive charge. Most of these peptides have alpha-helical structure; however, β-sheet and other structures have been observed among them. The mechanism of action of these antimicrobial agents is divided into two categories of membrane-based and intracellular target-based attack. Conclusion: Evidence from this review indicates that AMPs would be likely among the main anti- A. baumannii drugs in the post-antibiotic era. Also, the application of computer science to increase anti- A. baumannii activity and reduce toxicity could be helpful. Highlights: The world is heading towards a post-antibiotic era. A. baumannii is among the WHO list of bacteria for which new antibiotics are urgently needed. Antimicrobial peptides are highly potential to be used in anti- Acinetobacter drugs. Forty-six anti- Acinetobacter peptides were identified and classified into ten groups.